Influence of different lithium precursors on the crystal structure and ionic conductivity of Li7La3Zr2O12 solid electrolyte - Ha Eun Kang; Min Wook Kim; Ji Hyun Lee; Juchan Kwon; Young Soo Yoon (Energy Conversion and Management: X, 2025)
Garnet-type Li7La3Zr2O12 (LLZO) is a promising solid electrolyte for all-solid-state batteries (ASSBs). In this study, LLZO was synthesized via a solid-state reaction route using two different lithium precursors (Li2CO3 and LiOH), under both Ta,Al co-doping under identical conditions. Structural and surface characterizations revealed that the choice of precursor significantly influences phase purity and surface impurity formation, with LiOH based synthesis yielding fewer secondary phases and cleaner surfaces. Thermal analyses (TGA–DSC–DTG) combined with Coats–Redfern fitting indicated that LLZO synthesized with LiOH exhibited a lower activation energy (Ea) (15.0  kJ mol−1) for surface impurity decomposition than its Li2CO3-derived counterpart (59.7  kJ mol−1). Electrochemical impedance spectroscopy showed that Ta,Al co-doped LLZO prepared with LiOH exhibited the highest ionic conductivity 1.01 × 10−4 S cm−1 at 25 °C and 3.07 × 10−3 S cm−1 at 500 °C attributed to enhanced cubic phase stabilization and reduced interfacial resistance. These findings underscore the synergistic effect of lithium precursor selection and dopant engineering in optimizing LLZO performance offering practical guidance for the scalable fabrication of garnet-type solid electrolytes in next-generation ASSBs.